Chinese classics strange tales from the Liaozhai studio - Pu Songling (Chinese classics stories, 2017)
Strange Tales from the Liaozhai Studio is a collection of nearly five hundred mostly supernatural tales written by Pu Songling during the early Qing Dynasty. It is about the fairy-tales of ghost-fox. The book,on one hand,criticizes the bondages of feudal courtesy and the corruption of imperial examinations,and on the other advocates freedom and personality. The love stories are the favorite part of the readers. These stories feature in the love between humans and ghost-foxes,showing the wishes of the young men and women to break those feudal bondages. This book is edited and translated by the famous translator Wang Guozhen, to introduce Strange Tales from the Liaozhai Studio to the foreign readers.